Extreme insects: creepy and crawly, mad and bad! - Parker, Steve; Martin, Stuart (Newtown, N.S.W., Walker Books Australia, 2009)
Introduces the most interesting, ugly, and dangerous insects in the animal world, such as the super speedy dragonfly, the caterpillar that looks like a bird dropping, the botfly maggot, and the giant predatory centipede. Includes lift-the-flap illustrations and tabbed enclosures. Suggested level: primary, intermediate